Research framework - Falck-Zepeda, José B.; Horna, Daniela; Zambrano, Patricia (International Food Policy Research Institute, 2013)
An ex ante impact evaluation of any technology poses a number of challenges, and genetically modified (GM) crops are no exception. The most important and evident constraint when evaluating a technology that has not yet been deployed is the impossibility of using primary information to assess the behavior of the technology under farming conditions. In the case of GM crops, the best available data would be the information generated during confined field trials (CFTs), where GM varieties are tested after passing the regulatory approval process. The resulting information from these CFTs, although valuable, has its limitations. Even after a rigorous selection of sites, the whole diversity of agroecological and farming conditions cannot be captured. With limited availability of primary information, the ex ante evaluation has to rely on (1) expert opinions, (2) some assumptions about the technology’s future behavior based on its past performance in other locations; and (3) a modest amount of primary information collected from a few sites. This chapter presents a research framework that takes into account these specific limitations that most developing countries face.